Foreign terrorist fighters: phenomenon and legal countermeasures : a comparative study between Germany and China - Bai, Luyuan (Schriften zur Kriminologie, 2023)
"This book is the result of a study on the phenomenon of foreign terrorist fighters and the respective measures from a comparative perspective. The phenomenon triggered an international panic after the outbreak of the Syrian civil war. Fear and panic, especially when unprecedented, severe, or enduring, lead to mistrust and wrong decisions that have far-reaching effects. In this context, this book examines two questions: whether a comprehensive understanding of the phenomenon is at hand, which is a prerequisite for reasonable solutions, and whether the present legal responses to the problem are reasonable and responsible in terms of the rule of law"--Publisher's description